If f(x)3(=- Vx-3, complete the following statement:x + 2f(19) ==Answer here

Answers

Ihave, but this question is gonna probably get deleted.

step-by-step explanation:

i think something is missing in your question because y-1=(x-12) would not pass through the point (-4,-3). because if you replace x by -4 your are supposed to find y=-3 which is not the case her. if you replace x by -4 you find =-15.

i assume the right equation is y-1=1/4*(x-12) because this one is passing through both your points (if you are interested to know how i found that out i can tell you).

in this equation if i replace x by -4 i find y=-3 and if i replace x by 12, i find y=1 so the line representing this equation is passing through those 2 points.

then the standard form of the equation is finding an expression of y in function of x

y-1=1/4*(x-12)

y=x/4-3+1

y=x/4-2

hope that .

do you confirm there was a mistake in the question?

Explanation

This exercise is about evaluating a function at a particular argument. To do that, we replace the variable with the argument in the formula of the function, and simplify.

Let's do that:

\begin{gathered} f(19)=\frac{3}{19+2}-\sqrt[]{19-3}, \\  \\ f(19)=\frac{3}{21}-\sqrt[]{16}, \\  \\ f(19)=\frac{1}{7}-4, \\  \\ f(19)=\frac{1-28}{7}, \\  \\ f(19)=-\frac{27}{7}\text{.} \end{gathered}Answerf(19)=-\frac{27}{7}\text{.}


Do you know the answer?

Other questions on the subject: Mathematics

there are 25 people coming to the party step-by-step explanation: the text says that there will be 22 children at this party, 1 teacher, and 2 parents. so if you add them all toget...Read More
2 more answers
the solution is x=1step-by-step explanation: we are given our   equation as[tex]log_3(x)=(x)[/tex]let's assume left side function is [tex]f(x)=log_3(x)[/tex]right side functio...Read More
1 more answers